RACK1A positively regulates opening of the apical hook in Arabidopsis thaliana via suppression of its auxin response gradient - Qian Ma; Sijia Liu; Siamsa M. Doyle; Sara Raggi; Barbora Pařízková; Deepak Kumar Barange; Hemamshu Ratnakaram; Edward G. Wilkinson; Isidro Crespo Garcia; Joakim Bygdell; Gunnar Wingsle; Dirk Roeland Boer; et al. (Proceedings of the National Academy of Sciences, 2025)
Apical hook development is an ideal model for studying differential growth in plants and is controlled by complex phytohormonal crosstalk, with auxin being the major player. Here, we identified a bioactive small molecule that decelerates apical hook opening in Arabidopsis thaliana . Our genetic studies suggest that this molecule enhances or maintains the auxin maximum found in the inner hook side and requires certain auxin signaling components to modulate apical hook opening. Using biochemical approaches, we then revealed the WD40 repeat scaffold protein RECEPTOR FOR ACTIVATED C KINASE 1A (RACK1A) as a direct target of this compound. We present data in support of RACK1A playing a positive role in apical hook opening by activating specific auxin signaling mechanisms and negatively regulating the differential auxin response gradient across the hook, thereby adjusting differential cell growth, an essential process for organ structure and function in plants.